Chitosan microspheres with an extracellular matrix-mimicking nanofibrous structure as cell-carrier building blocks for bottom-up cartilage tissue engineering. Issue 1 (27th November 2015) - Zhou, Yong; Gao, Huai-Ling; Shen, Li-Li; Pan, Zhao; Mao, Li-Bo; Wu, Tao; He, Jia-Cai; Zou, Duo-Hong; Zhang, Zhi-Yuan; Yu, Shu-Hong
Abstract : Bulk cartilage-like tissue composites can be constructed from ECM-mimicking nanofibrous chitosan microspheres from physical gelation by co-culturing them with chondrocytes in vitro . Abstract : Scaffolds for tissue engineering (TE) which closely mimic the physicochemical properties of the natural extracellular matrix (ECM) have been proven to advantageously favor cell attachment, proliferation, migration and new tissue formation. Recently, as a valuable alternative, a bottom-up TE approach utilizing cell-loaded micrometer-scale modular components as building blocks to reconstruct a new tissue in vitro or in vivo has been proved to demonstrate a number of desirable advantages compared with the traditional bulk scaffold based top-down TE approach. Nevertheless, micro-components with an ECM-mimicking nanofibrous structure are still very scarce and highly desirable. Chitosan (CS), an accessible natural polymer, has demonstrated appealing intrinsic properties and promising application potential for TE, especially the cartilage tissue regeneration. According to this background, we report here the fabrication of chitosan microspheres with an ECM-mimicking nanofibrous structure for the first time based on a physical gelation process. By combining this physical fabrication procedure with microfluidic technology, uniform CS microspheres (CMS) with controlled nanofibrous microstructure and tunable sizes can be facilely obtained. Especially, no potentially toxic or denaturizing chemical crosslinking agent was introduced into the products. Notably, in vitro chondrocyte culture tests revealed that enhanced cell attachment and proliferation were realized, and a macroscopic 3D geometrically shaped cartilage-like composite can be easily constructed with the nanofibrous CMS (NCMS) and chondrocytes, which demonstrate significant application potential of NCMS as the bottom-up cell-carrier components for cartilage tissue engineering.